Pengembangan Media Puzzle Akrilik Untuk Meningkatkan Kreativitas Siswa Kelas IV SDN Jembatan Lima 03 Jakarta Pada Materi Bangun Datar - Sulistia, Aulia Feidah; Ritonga, Rudi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to develop an Acrylic Puzzle-based learning media and determine its effectiveness in improving the creativity of fourth-grade elementary school students in learning about plane shapes. The research was motivated by the lack of concrete and interactive media in mathematics learning, which often results in passive student participation and difficulty in understanding geometric concepts. The Acrylic Puzzle was designed to allow students to physically assemble and deconstruct two-dimensional shapes, making the learning process more enjoyable and meaningful. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants were fourth-grade students at SDN Jembatan Lima 03 Jakarta. Data were collected through observation, documentation, interviews, and pretest-posttest assessments of student creativity. The results showed that the Acrylic Puzzle media was both feasible and effective. Average creativity scores increased significantly, from 65.62 to 86.56 in the small-scale trial and from 69.69 to 92.18 in the large-scale trial. These findings suggest that the Acrylic Puzzle can serve as an effective interactive learning tool to support students’ creativity and understanding of two-dimensional shapes.